1960
DOI: 10.1785/bssa0500020221
|View full text |Cite
|
Sign up to set email alerts
|

Alaska earthquake of July 10, 1958: Intensity distribution and field investigation of northern epicentral region

Abstract: The 10 July 1958 earthquake centered near Lituya Bay, Alaska, produced moderate property damage at Yakutat, 100 miles to the northeast, and was readily felt within 400 miles of the epicenter. Five persons died during the earthquake: two in Lituya Bay, where a cataclysmic wave sank two fishing vessels; three others near Yakutat, when a beach on which they were standing fell 100 feet beneath the sea. The earthquake caused large slides in the mountain areas and produced great numbers of sandblows and fissures on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1965
1965
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A few toppled chimneys that we observed in Port Chilkoot may have fallen during this quake. Intensity at Skagway was given as VI (Davis and Sanders, 1960). The same or a slightly higher intensity for similar geologic units in Haines seems reasonable.…”
Section: S3mentioning
confidence: 92%
“…A few toppled chimneys that we observed in Port Chilkoot may have fallen during this quake. Intensity at Skagway was given as VI (Davis and Sanders, 1960). The same or a slightly higher intensity for similar geologic units in Haines seems reasonable.…”
Section: S3mentioning
confidence: 92%
“…It was suggested that this larger event was a multi‐fault slip event, triggered on local reverse faults, in a region with high strain‐partitioning (Walton et al., 2022). In 1958, there was an M 7.9 event that triggered the destructive tsunami in Lituya Bay and ruptured between 250 and 370 km of the Fairweather fault (Davis & Sanders, 1960; Doser, 2010; Stauder, 1960). Finally in 1979, there was a series of strike‐slip and low‐angle thrust events in the Pamplona fault zone (Doser et al., 1997; Doser & Lomas, 2000).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Equipment left by a mining company at an intended campsite on the south shore was also washed away. Davis and Sanders (1960) report that when they flew over the area on July 12, the ocean beaches for 10 miles on both sides of the mouth of Lituya Bay were covered with ice and trees stripped of their bark. Ice and trees were also being carried seaward at right angles to the coast.…”
Section: P 1) Carried Swanson's Accountmentioning
confidence: 99%
“…Two fled to their boat and spent several hours riding out the swells. The third man tried to save their equipment but lost much to 5-foot waves (Davis and Sanders, 1960). These were probably small tsunami waves generated by the falling ice from the glacier.…”
Section: P 1) Carried Swanson's Accountmentioning
confidence: 99%